H-reflex up-conditioning encourages recovery of EMG activity and H-reflexes after sciatic nerve transection and repair in rats. - Yi Chen; Wang, Yu; Lu Chen; Sun, Chenyou; English, Arthur W.; Jonathan Wolpaw; Xiang Yang Chen (The Journal of neuroscience : the official journal of the Society for Neuroscience, 2010)
Operant conditioning of the spinal stretch reflex or its electrical analog, the H-reflex, produces spinal cord plasticity and can thereby affect motoneuron responses to primary afferent input. To explore whether this conditioning can affect the functional outcome after peripheral nerve injury, we assessed the effect of up-conditioning soleus (SOL) H-reflex on SOL and tibialis anterior (TA) function after sciatic nerve transection and repair. Sprague Dawley rats were implanted with EMG electrodes in SOL and TA and stimulating cuffs on the posterior tibial nerve. After control data collection, the sciatic nerve was transected and repaired and the rat was exposed for 120 d to continued control data collection (TC rats) or SOL H-reflex up-conditioning (TU rats). At the end of data collection, motoneurons that had reinnervated SOL and TA were labeled retrogradely. Putative primary afferent terminals [i.e., terminals containing vesicular glutamate transporter-1 (VGLUT1)] on SOL motoneurons were studied immunohistochemically. SOL (and probably TA) background EMG activity recovered faster in TU rats than in TC rats, and the final recovered SOL H-reflex was significantly larger in TU than in TC rats. TU and TC rats had significantly fewer labeled motoneurons and higher proportions of double-labeled motoneurons than untransected rats. VGLUT1 terminals were significantly more numerous on SOL motoneurons of TU than TC rats. Combined with the larger H-reflexes in TU rats, this anatomical finding supports the hypothesis that SOL H-reflex up-conditioning strengthened primary afferent reinnervation of SOL motoneurons. These results suggest that H-reflex up-conditioning may improve functional recovery after nerve injury and repair.
Keywords: conditioning; peripheral nerve; plasticity; Reflex; regeneration; Spinal Cord

Operant conditioning of rat H-reflex: effects on mean latency and duration. - Jonathan Wolpaw; Xiang Yang Chen (Experimental brain research. Experimentelle Hirnforschung. Expérimentation cérébrale, 2001)
We are currently studying the mechanisms of operantly conditioned changes in the H-reflex in the rat. Primate data suggest that H-reflex decrease is due to a positive shift in motoneuron firing threshold and a small decrease in the monosynaptic excitatory postsynaptic potential (EPSP), and that increase might be due to change in group-I oligosynaptic (especially disynaptic) input. To further evaluate the possibility of conditioned change in oligosynaptic input, we compared the mean latency (i.e., the average latency of the entire H-reflex) and the duration of control (i.e., pre-conditioning) H-reflexes with those of H-reflexes after up-conditioning or down-conditioning. Up-conditioning was associated with small, statistically significant increases in H-reflex mean latency [+0.11+/-0.05 (+/-SE) ms] and duration (+0.32+/-0.16 ms). The mean latency of the H-reflex increase (i.e., the part added to the H-reflex by up-conditioning) was 0.28+/-0.14 (+/-SE) ms greater than that of the control H-reflex. Down-conditioning had no significant effect on mean latency or duration. While these results indicate that operant conditioning does not greatly change H-reflex mean latency or duration, the effects detected with up-conditioning are consistent with the hypothesis that decreased inhibition, or increased excitation, by homonymous and heteronymous group-I oligosynaptic input contributes to the H-reflex increase produced by up-conditioning. Several other mechanisms might also account for these small effects.
Keywords: conditioning; H-Reflex; Memory; plasticity; Spinal Cord

Time course of H-reflex conditioning in the rat. - Xiang Yang Chen; Lu Chen; Jonathan Wolpaw (Neuroscience letters, 2001)
This study sought to define the course of operantly conditioned change in the rat soleus H-reflex and to determine whether, like H-reflex conditioning and spinal stretch reflex conditioning in the monkey, it develops in distinct phases. Data from 33 rats in which the right soleus H-reflex was trained up (i.e. HRup mode) and 38 in which it was trained down (i.e. HRdown mode) were averaged to define the courses of H-reflex increase and decrease. In HRup rats, the H-reflex showed a large phase I increase within the first 2 days followed by gradual phase II increase that continued for weeks. In HRdown rats, the H-reflex appeared to show a small phase I decrease and then showed a gradual phase II decrease over weeks. In combination with other recent work, the data suggest that H-reflex conditioning begins with a rapid mode-appropriate alteration in corticospinal tract influence over the spinal arc of the H-reflex, which causes phase I change, and that the continuation of this altered influence induces gradual spinal cord plasticity that is responsible for phase II change. The results further establish the similarity of H-reflex conditioning in primates and rats. Thus, they encourage efforts to produce a single coherent model of the phenomenon based on data from the two species and indicate the potential clinical relevance of the rat data.
Keywords: conditioning; Learning; Memory; plasticity; rat; Reflex; Spinal Cord